Tracheostomy as a Comfort Measure in Children With Life-Limiting Conditions. Issue 3 (July 2017) - Marshall, Valerie; Holt, Francesca; Crowe, Suzanne
Palliative care for children who can expect only a short life has expanded over the last decade. Greater understanding of the measures required to ensure comfort and acceptable quality of life within the critical care environment has grown in tandem. Some more invasive interventions may be considered a "step too far" by some practitioners, including feeding gastrostomy, contracture release, and tracheostomy. Tracheostomy can facilitate a number of measures, which may enhance the brief life of the child and their family. However, tracheostomy is associated with some challenges, which may make it less suitable for some families. We discuss 3 cases where this intervention was carried out.